THE USE OF DIFFERENT pH VALUES ON THE ISOELECTRIC POINT OF THE PROTEIN ISOLATES MUDSKIPPER FISH (Periopthalmus minutus) - Teresia Br Ginting; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT   This study aimed to determine isolates of the mudskipper fish protein (Periopthalmus minutus) with different pH values. This methods was of this research consist of three  stages, that is: 1) fish meat preparation. 2) manufacture mudskipper flour. 3) making fish isolates. This research used a completely  randomized design (CRD) with 6 levels of treatment that is:(P1 = pH 9 and pH 4, P2 = pH 9 and pH 5, P3 = pH 10 and pH 4, P4 = pH 10 and pH 5 , P5 = pH 11 and Ph 4, P6 = pH 11 and pH 5. The parameters observed included isolates total, yield, proximate and total amino acids.The results showed that pH 11 and pH 4 obtained the highest isolates that was average of 6.54 g with a yield of 19.62%.  Proximate result were moisture content 5.16% (bb), ash content 7.06% (bb), protein content 82.39% (bb ), fat content of 1.62% (bb) and total amino acid content of 61.63%,wich dominates essential amino acids were lysine 6.79% and leucine 5.60%. The dominates non-essential amino acids were glutamic acid 10.77 % and aspartic acid 4.65%. Keywords :Mudskipper, pH,protein isolates